O aprendizado em organizações certificadas pela NBR ISO 9001:2000 - Turcato, Cristina Rodrigues da Silva (2008)
This dissertation consists of a multi-case study accomplished in three companies located in the city of Panambi/RS. The main objective of the study is to analyze the process of organizational learning inside of the companies certified by NBR ISO 9001:2000, identifying procedures that, if better managed, could propitiate improvements in the company, with reflexes in the organization acting. The investigated variables were Strategic Intention and the Objectives of the Learning, Components of the Learning, Viability of the Learning, Culture of the Organization and Administration of the Learning, this questionnaire was divided in five dimensions and applied in the companies certified by NBR ISO 9001:2000. The research was accomplished through the interview of the 400 collaborators of the researched companies. For the descriptive statistical analysis of the data was used the software, Sphinx Lexical and for multivariate analysis was used the software Statistica 7.0. The descriptive analysis applied to the collaborators in the companies A, B and C is observed that the organizational learning is present inside of the researched organizations and identifying the individual's importance for the organizational development. Considering the dimensions attributed in the questionnaire, conclude that the aspects of the results has a great influence in the evaluation of the organizational learning, from the managers as well as from the collaborators. Comparing the importance level, it was verified that the companies had very important estimates obtaining a satisfactory result for the company. This data represents how important is the collaborators' expectations for the organizational learning. In the cluster analysis, was important in the identification of the similar question that provided a reduction in the number of question. Before the Analysis of Cluster to be applied the calculation of the alpha of Cronbach was applied to verify if the results of the questionnaires were coherent. When the method of linkage simple was applied, variables with the same degree of information was excluded, and it was obtained α = 0,75. Analyzing the method linkage simple, all of the questionnaire dimensions was presented, without being other dimensions classified. The Analysis of Cluster identified the variables that belong to the same cluster facilitating, with this, to discover if they have the same purpose. After the retreat of variables with the same purpose inside of each cluster, it was obtained the formation of a new questionnaire, which was appropriate for a new research, turning the most representative work in relation to the first application. The presented data, in the descriptive analysis and cluster analysis, give us the conclusion d that the objective of this work, initially proposed, was fully reached, theoretically as well as in the research field, both were approached and debat